An Early Warning Scheme for Broadcasting Critical Messages using VANET. (6th July 2010) - Chou, Li-Der; Ho, Ching-Chiang; Chen, Jui-Ming
Traffic safety improvement is the most critical application of Vehicular Ad-hoc Network (VANET). Using VANET, the information of a sudden vehicle braking can be broadcasted to neighbouring vehicles to avoid further accidents earlier. Most of the current researches did not consider about the delivery time and the human influence like driver reaction time or the brake intensity. In the paper, an Early Warning scheme for Broadcasting Critical Messages (EWBCMs) scheme is proposed to reduce the latency of message transmission. Simulation results show that the EWBCM can reduce the delivery time, the packet loss rate and the receiving failure rate effectively.